A negociação de identidades de professor na sala de aula de estágio de língua espanhola - Lopes, Marcela de Freitas Ribeiro (2009)
Current dissertation is part and parcel of a working process between the classroom, school and Spanish language teacher training. Final year students of the Spanish language course always considered that they became students during the Spanish Language Trainee activities. Current essay investigates the negotiation of identity in speech-in-interaction in trainee activities of three last year Spanish Language course students of the Western-Central State University (UNICENTRO) at Irati PR Brazil. Current analysis is foregrounded on two theoretical bases, namely, Ethnomethodological Conversation Analysis and Interactivity Sociolinguistics which serve as a basis for the speech-in-interaction analysis of the future teachers' classroom and for investigation of the teacher's identity which they negotiate and construct with the students. Field work was undertaken with six upper high school groups in three public schools of Irati PR Brazil. Thirty-one hours/classes of audiovisual recordings were collected after the consent of the principals, teachers, trainees and children's parents of the student concerned. Analysis of lessons showed that (1) the three trainees orchestrate the students' stage and speech-in-interaction occurs according to a determined order established by the trainee participating student; (2) students participate in the orchestration and maintain the category of the organizer of the trainees' interactivity - the teachers' identity is thus corroborated; (3) speech-in-interaction harbors conflicts and the teachers of the groups present in the classroom intervene in the trainees' identity, whereas the students subvert the status of the knowledgeable ones and of the speech-in-interaction organizers; (4) each training teacher has her own teaching and learning proposal related to what each one of them thinks on what it is like being a teacher; this proposal is negotiated in the speech-in-interaction with students and the group's teacher. Since the teachers' identity is thus formed during the trainee period, it reveals that training teachers should undertake discussions on speech-in-interaction, participation and social identities.